Improving nutrition through biofortification: Preharvest and postharvest technologies - Listman, G. Michael; Guzmán, Carlos; Palacios-Rojas, Natalia; Pfeiffer, Wolfgang H.; San Vicente, Felix; Velu, Govindan (AACC International, 2019)
More than 2 billion people worldwide suffer from “hidden hunger,” wherein they fail to obtain enough nutrients or micronutrients from the foods they eat. Biofortification—the development of micronutrient-dense staple crops using traditional breeding practices and modern biotechnology—is a promising approach to improve nutrition, as part of an integrated, food systems strategy. In work begun in the late 1990s, the CGIAR institutions HarvestPlus, the International Maize and Wheat Improvement Center (CIMMYT), and the International Institute of Tropical Agriculture (IITA), together with numerous national research organizations and scaling partners, have in recent years developed and released in 19 countries in Africa, Asia, and Latin America more than 60 improved varieties of maize and wheat whose grains feature enhanced levels of the essential micronutrients zinc or provitamin A. Use of these varieties is spreading among farmers and consumers, many of whom have diets that lack micronutrients because they cannot afford diverse foods and depend heavily on foods made from staple crops. Eating provitamin A-rich maize has been shown to be as effective as supplementation, and a 2018 study in India found that using zinc-biofortified wheat to prepare traditional foods can significantly improve children’s health